Estimation of actual evapotranspiration by numerical modelling of water flow in the unsaturated zone - Guarracino, Luis (2007)
The objective of this paper is to present a model to estimate actual evapotranspiration ETA from reference evapotranspiration ET0 by numerical modelling of water flow in the unsaturated zone of the soil. Water flow is described by the highly non-linear Richards equation with a sink term representing the root water uptake. Evaporation is included in the model as a Neumann boundary condition at the soil surface. Richards equation is solved in a one-dimensional domain using a mixed finite element method. The values of ETA are obtained by applying a water stress factor to ET0 to account for soil moisture changes during simulation period. The proposed numerical model is used to estimate ETA in an experimental plot located in a flatland area in Buenos Aires (Argentina). Numerical results show that the proposed model is a useful tool for evaluating evapotranspiration under different scenarios.